Humidity‐Driven High‐Performance Electrothermal Actuation of Vertically Stacked 2D PtTe2 Layers/Cellulose Nanofibers. (18th January 2023) - Yoo, Changhyeon; Han, Sang Sub; Okogbue, Emmanuel; Bae, Tae-Sung; Jang, Jae Hyuck; Cao, Justin; Chung, Hee-Suk; Jung, Yeonwoong
Abstract : A new type of soft actuators based on a vertical stack of nanoporous 2, 2, 6, 6‐tetramethylpiperidine‐1‐oxyl‐oxidized cellulose nanofibers (TOCNs) and atomically thin 2D platinum ditelluride (PtTe2 ) layers is reported. The actuation of TOCNs is driven by the interfacing 2D PtTe2 layers whose electrothermal proficiency precisely controls their hydration/dehydration states sensitive to mechanical deformation. These vertically stacked TOCN/2D PtTe2 actuators present excellent actuation characteristics such as high linearity of bending curvature versus applied voltage and well‐preserved reversibility during cyclic operations. Most notably, they exhibit an extremely large weight‐lifting ratio, i.e., ≈1000 times the mass of the TOCN layers, confirming superior mechanical robustness. Furthermore, complicated actuations such as twisting in a 3D manner are demonstrated by judiciously controlling the surface wettability of TOCN layers. This study unveils opportunities for CNFs and 2D materials for actuator applications, as well as suggests new design strategies broadly applicable to soft robotics and biomimetic devices. Abstract : A new type of bimorph actuator operated by the actuation of cellulose nanofibers (CNFs) driven by the Joule heating of ultrathin 2D PtTe2 layers sandwiched between CNFs and the polymer is reported.